Public cost of privately inserted laparoscopic adjustable gastric bands. Issue 3 (4th March 2019) - Patel, G.; Tase, A.; Caplin, S.; Barry, J.
Abstract : Background: Laparoscopic adjustable gastric banding (LAGB) remains a commonly performed procedure for morbid obesity. Concerns regarding its long‐term consequences include high rates of band removal from complications and failure to lose weight. Many private practices continue to perform LAGB but, owing to short follow‐up periods, the burden of surgical complications falls upon National Health Service (NHS) bariatric units. This study aimed to review the NHS treatment of patients for complications related to privately performed LAGB. Methods: All surgical complications following bariatric surgery referred to the Welsh Institute of Metabolic and Obesity Surgery (WIMOS) between September 2010 and September 2014 were reviewed. Type of complication, procedures performed, and number of outpatient attendances and inpatient stays were recorded. Costs of treatment were estimated using standard tariffs. Results: A total of 78 patients presented with complications after privately performed bariatric surgery. Sixty had undergone LAGB; the remainder had had other bariatric procedures. Median age was 45 (range 22–78) years, and 65 (83 per cent) were women. Urgent band deflation was undertaken in 53 patients. Band removal surgery was required in 32 patients; one patient needed a subtotal gastrectomy. There was a total of 123 outpatient/ward attendances and 340 days of inpatient care, including 10 days of intensive care. The estimated total cost to the NHS of managing these patients was €337 400 (€84 350 per annum). Conclusion: The cost burden to the NHS of managing the complications of bariatric surgery performed in the private sector is considerable. Although it is imperative that such complications be managed in well equipped specialist units, private surgery providers should have better follow‐up plans and/or contractual agreements with the NHS. Abstract : Laparoscopic adjustable gastric banding remains a commonly performed procedure for morbid obesity in the private sector. Concerns exist regarding its complications and the cost implication of their management by National Health Service (NHS) bariatric services. This cost is considerable and better follow‐up plans and/or contractual agreements with the NHS to treat complications should be drafted by private surgery providers. NHS foots bill for private practice complications